Social and Economic Determinants of Business Risk-Taking Propensity Among Entrepreneurs of Small and Medium Scale Enterprises in Akoko Region, Ondo State, Nigeria - Omolawal, Samuel Ayodeji (Journal of Applied And Theoretical Social Sciences, 2023)
This study investigated social and economic determinants of business risk-taking propensity among Entrepreneurs of Small and Medium scale Enterprises (SMEs) in Akoko Region, Ondo State. It utilised descriptive research design. Study population comprised SMEs entrepreneurs in the four local governments making up the study location. Collection of primary data was done using Questionnaire administered on randomly selected 241 respondents and 8 in-depth interviews. Quantitative data were analysed with descriptive statistics involving T-test of independent measures while qualitative data were content analysed. Younger entrepreneurs expressed higher levels of risk-taking propensity than their older counterparts [t (241) =4.47; p<.05]; Male entrepreneurs expressed higher degree of risk-taking propensity than their female counterparts [t (241) =1.577; p<.05]; highly experienced entrepreneurs expressed lower level of risk-taking propensity than their less experienced counterparts [t (241) =3.02; p<.05]. However, there was no significant influence of education [t (241) =1.099; p<.05]; and religious leaning [t (241) =1.062; p<.05] on risk-taking propensity among entrepreneurs. Also, financial capital [β = .091, t=1.385], stability of electricity [β = .020, t=.329], business location [β =.191, t =2.418], customer base [β = .041; t=.642], and market competition [β = -.146], were low predictors of risk-taking propensity. SMEs entrepreneurs are enjoined to master their entrepreneurial domain, the knowledge of which will enhance their risk-taking propensity.